A REPLENISHMENT POLICY WITH TWO-STAGE CONSUMPTION RATES FOR PARTIALLY REPAIRED NON-INSTANT DECAYING GOODS AND VARYING STORAGE COST UNDER ALLOWABLE PAYMENT DELAY - Zulkifilu Muazu; Mustapha Mannir Gafai; Bature Babangida (FUDMA Journal of Sciences, 2025)
Many inventory models for deteriorating items are developed on the assumptions that deteriorated items are not fixed or replaced; instead, they are thrown away and inventory carrying costs are not considered while developing inventory policies. However, in real-world, deteriorated items such as roofs, ceilings, doors, locks, windows, plumbing pipes and taps, electronics, desks, seats, spare parts, and so on are repairs or replaced. Similarly, carrying charges affect inventory total cost, influence order quantity, determine the level of stock to keep, and influence profit, pricing, and budgeting decisions, thus their impact cannot be overlooked when designing inventory policies. In this work, a two-stage consumption rate replenishment policy with variable storage costs under allowable payment delays is examined for partially repaired non-instantaneous decaying goods. Prior to product deterioration, the rate of consumption is a quadratic function of time, and it remains constant thereafter after that. The main aim of this model is to identify optimal cycle length and order quantity amount that minimize the overall variable cost. It is established that solution exist and are unique solutions exist and are distinct. The model is validated using numerical test based on tests of some existing data, and a comparison with the current model reveals that the proposed model performs better in terms of cost minimization and turnover. Some suggestions for lowering the total variable cost of the inventory system are provided based on in light of the sensitivity analysis.